Antioxidant Potential of Jicama (Pachyrhizus erosus) Extract Fermented by Lactobacillus plantarum B1765 - Aji, Ardika Prasetya; Wikandari, Prima Retno (Jurnal Pijar Mipa, 2024)
Jicama is a source of phenolic compounds that function as antioxidants. However, the presence of polyphenol oxidase and naturally bound phenolic compounds limits its antioxidant potential. Fermentation is one method to enhance the antioxidant potential of jicama. This study investigates the growth of lactic acid bacteria (LAB), pH, total titratable acidity (TTA), total phenolic content (TPC), and antioxidant activity of jicama extract (Pachyrhizus erosus) using L. plantarum B1765 as a starter culture which was fermented for 2, 12, 24, and 36 hours at 37°C. Total LAB is measured using the whole plate count technique, pH using a pH meter, TTA by acid-base titration, TPC using the Folin-Ciocalteu method, and antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method represented by IC50. The fermentation duration of jicama extract increased the growth of LAB to 108 CFU/mL and reached its optimum at 12 hours. However, reducing pH, increasing TTA to 0.223%, increasing TPC, and antioxidant activity still occur up to 36 hours of fermentation. Antioxidant activity was classified as vital. Duration of fermentation increased the growth of total LAB until the defined time, secreted β-glucosidase and inulinase enzymes, and also produced acid as their metabolism product, which hydrolyzed the glycoside bond and reduced pH, both act to free phenolic and increased antioxidant activity. This product has met Indonesian National Standards for beverage-fermented types and could be an antioxidant agent.